Can the major public works policy buffer negative shocks in early childhood? Evidence from Andhra Pradesh, India - Dasgupta, A (Young Lives, 2013)
The study examines the role of the largest public works program in the world-the National Rural Employment Guarantee Scheme (NREGS) - in buffering the negative effects of early childhood exposure to rainfall shocks on long-term health outcomes. Exploiting the spatial and temporal variation in NREGS coverage, the study estimates the extent to which nutritional shocks in early childhood can be offset by access to the policy. The study employs a unique identification strategy by integrating detailed administrative records of drought shock and phase-wise roll-out information of NREGS with a household level panel data-the Young Lives survey- conducted over three waves (2002, 2007 and 2009-10) in the state of Andhra Pradesh, India. Using individual fixed effects estimation the study finds that while the policy does not help correct for long term past health deficiencies it is useful in buffering recent drought shocks, which varies by policy relevant sub-groups. We find that an increase in 22 working days per household increases height-for-age by around 0.26 standard deviations which is bridging about half the rural-urban gap in average height for age score.We find the program is most effective for the case of lower educated households and scheduled castes, who are presumably more vulnerable in the face of climatic variability. Hence there is much room to reap in the indirect benefits of the program by ensuring food security issues of these households.